Treatment of Nevus Spilus with dual-wavelength copper vapor laser - Igor V. Ponomarev; Sergey B. Topchiy; Yury N. Andrusenko; Lyudmila D. Shakina (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Introduction. Speckled lentiginous nevus or Nevus Spilus (NS) is a congenital or acquired melanocytic nevus. NS appears as dark hyperpigmented macules or papules interspersed in the lentigo-like hyperpigmentation patch. Surgical methods for removing NS, primarily on the skin with a thin dermis, are associated with the risk of disruption of its structure or scarring. The use of single wavelength laser irradiation allowed achieving pronounced bleaching of the NS area with such side effects as scars, post-inflammatory hyperpigmentation, and relapses in some cases. Side effects could occur due to the lack of complete blood flow in the microvascular bed near the NS. The study aimed to evaluate the efficacy of NS treatment with a dual-wavelength copper vapor laser (CVL). Description of patients and the method of the treatment. Two fair-skinned adult female patients with NS, of medium size and different location, asked to restore the natural colour of the skin in order to get rid of cosmetic defects. NS treatment was carried out using CVL (Yakhroma-Med model, P.N.Lebedev Physical Institute of the Russian Academy of Sciences) during six procedures, an interval of 46weeks. For treatment, we used two-wavelength CVL radiation with average power in the range of 0.60.8W with a power ratio of 3:2 at wavelengths of 511 nm and 578 nm; exposure time: 0.20.3 s. The diameter of the light spot on the skin accounted for 1 mm. Both patients were satisfied with the result of the treatment due to the noticeable blanching of the pigmented skin area after the NS removal. During the following two years, no dark spots or scarring was observed at the NS removal site. Conclusion. Treatment of medium-sized NS using two-wavelength CVL radiation made it possible toeliminate the cosmetic defect without side effects.